Promocja turystyczna w działalności bieszczadzkich jednostek samorządowych - Szwichtenberg, Aleksander (Tourism Promotion in the Activities of Local Selfgovernment Units in the Region of Bieszczady, 2005)
The article presents survey results comprising an analysis of promotional activities taken up by alI communes in Bieszczady region and Krosno - the main urban centre of Bieszczady. The author provides thorough characteristics of the researched area, as well a definition of the region' s level of tourism function development. The article outlines investments into promotion in the researched communes in 2003 and compares the expenditure on promotion to the one in 2002. The also defines promotional activities taken up by the communes of Bieszczady and undertakes an attempt of recognizing markets towards which they direct their offer. The area is not very frequently visited by tourists, which to a great extend results from the standard way of tourism promotion and smalI investments into it carried out by local authorities.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1067, s. 170-181